Basic Principles of Processed Electroencephalography for Neuroanesthesiologists - Pramodana, Bintang; Fuadi, Iwan (https://snacc.org/wp-content/uploads/2019/fall/Intl-news3.html, 2026)
Processed electroencephalography (pEEG) has become an integral tool in modern anesthesia and critical care, enhancing the precision of anesthesia depth monitoring, reducing the risk of accidental awareness under general anesthesia (AAGA), and postoperative cognitive issues. Unlike raw EEG, which records cortical electrical activity directly, pEEG applies mathematical and algorithmic analyses, such as spectral analysis and Fourier transformation, to generate numerical indices that are more interpretable for clinicians. Several commercial systems, including the Bispectral Index (BIS), Entropy, Conox, and SedLine, are widely available. For neuroanesthesiologists, understanding core EEG principles and advanced metrics, such as the Density Spectral Array (DSA), Spectral Edge Frequency (SEF), and Burst Suppression Ratio (BSR), is crucial for accurate interpretation. Moreover, recognizing EEG patterns characteristic of various anesthetic agents, including propofol, inhaled agents, dexmedetomidine, ketamine, and opioids, further refines clinical decision-making. Mastery of EEG interpretation ultimately supports better safety, individualized neuroanesthesia practice aligned with the principles of precision medicine